Effect of Voluntary Human Policy Disclosure on Firm Value: Case Study in Vietnam - Pham Thi Thuy Hang; Pham Thi Bich Duyen (My University, 2023)
Effect of Voluntary Human Policy Disclosure on Firm Value: Case Study in Vietnam
Keywords: Human policy disclosure